Acculturation is associated with left ventricular mass in a multiethnic sample: the Multi-Ethnic Study of Atherosclerosis. Issue 1 (December 2015) - Effoe, Valery; Chen, Haiying; Moran, Andrew; Bertoni, Alain; Bluemke, David; Seeman, Teresa; Darwin, Christine; Watson, Karol; Rodriguez, Carlos
Abstract Background Acculturation involves stress-related processes and health behavioral changes, which may have an effect on left ventricular (LV) mass, a risk factor for cardiovascular disease (CVD). We examined the relationship between acculturation and LV mass in a multiethnic cohort of White, African-American, Hispanic and Chinese subjects. Methods Cardiac magnetic resonance assessment was available for 5004 men and women, free of clinical CVD at baseline. Left ventricular mass index was evaluated as LV mass indexed by body surface area. Acculturation was characterized based on language spoken at home, place of birth and length of stay in the United States (U.S.), and a summary acculturation score ranging from 0 = least acculturated to 5 = most acculturated. Mean LV mass index adjusted for traditional CVD risk factors was compared across acculturation levels. Results Unadjusted mean LV mass index was 78.0 ± 16.3 g/m2 . In adjusted analyses, speaking exclusively English at home compared to non-English language was associated with higher LV mass index (81.3 ± 0.4 g/m2 vs 79.9 ± 0.5 g/m2, p  = 0.02). Among foreign-born participants, having lived in the U.S. for ≥ 20 years compared to < 10 years was associated with greater LV mass index (81.6 ± 0.7 g/m2 vs 79.5 ± 1.1 g/m2, p  = 0.02). Compared to those with the lowest acculturation score, those with the highest score had greater LV mass index (78.9 ± 1.1 g/m2 vs 81.1 ± 0.4 g/m2, p  = 0.002). There was heterogeneity in which measure of acculturation was associated with LV mass index across ethnic groups. Conclusions Greater acculturation is associated with increased LV mass index in this multiethnic cohort. Acculturation may involve stress-related processes as well as behavioral changes with a negative effect on cardiovascular health.